EUCALIPYTUS LITTER CONTRIBUTION TO THE INTEGRATED CROP-LIVESTOCK SYSTEM - Wink, Charlote; Tonini, Helio; Damascena, Flavia de Souza; Morales, Marina Moura (Floresta, 2019)
The aim of this study is to assess eucalyptus litter and nutrient deposition on a monthly basis, at the age 47 to 58 years, in integrated eucalyptus with crop system (ICF), eucalyptus with livestock (ILF) and eucalyptus monoculture (F). Integration system data were compared through t test and compared to eucalyptus monoculture through ANAVA and Duncan test, at 5% probability level. Annual litter deposition reached 0.63 t ha-1 year in CFI, 0.43 t ha-1 year in LFI and 6.34 t ha-1 year in the monoculture system. The total and fractioned litter deposition in integration systems (0.19 to 0.26 kg.m-2) was significantly different from the monoculture system (0.63 kg.m-2) at collector area level, however, integration systems did not differ from one another at hectare level. The same trend was observed for nutrient stock in different compartments of the assessed litter. Regardless of the production system, the leaf fraction was the most representative factor in litter composition, which was followed by branches and bark. Nutrient content was similar among the tested treatments. Finally, nutrient stock was higher in the monoculture system; the highest nutritional contribution was observed in CFI between the assessed integration systems.